Una celebración mestiza del Cruz-Velakuy en el Cusco - Núñez del Prado Béjar, Juan Víctor (1969)
The present work proposes to expose a series of facts from the inter-class relationship in a traditional festivity of Cusco, which originally belonged to the chola class. In the present case, she has been adopted by a circle of middle-class mestizos. For this, we will first make a description of the development of said party and then on this background, we will project the phenomena in question.